2022
DOI: 10.1002/csc2.20790
|View full text |Cite
|
Sign up to set email alerts
|

Review of cool‐season turfgrass water use and requirements: II. Responses to drought stress

Abstract: Knowledge of drought resistance of cool-season turfgrasses is important because drought stress can occur wherever they are grown even in humid regions with wet climates. This review is Part II of two companion papers that review water use and requirements in cool-season turfgrasses. Part I presented the history of early water conservation and quantification methods in turfgrass and then summarized research results since 1980 on cool-season turfgrass evapotranspiration and deficit irrigation. Part II presents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…Consistent with our results, Norton et al 35 and Reed et al 36 reported partial S/SP in Festuca arundinacea . Other studies have addressed summer dormancy in Kentucky bluegrass 37 39 and Perennial ryegrass 40 . It also reported that some cool-season grass species from the Mediterranean basin such as Festuca arundinacea Schreb.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, Norton et al 35 and Reed et al 36 reported partial S/SP in Festuca arundinacea . Other studies have addressed summer dormancy in Kentucky bluegrass 37 39 and Perennial ryegrass 40 . It also reported that some cool-season grass species from the Mediterranean basin such as Festuca arundinacea Schreb.…”
Section: Discussionmentioning
confidence: 99%
“…ryegrass, will need adaptation to deficit irrigation for continued production in irrigated settings (Braun et al, 2022a;2022b). We found substantial variation within these populations for each of the four traits and found that the population variation was the largest source of variation for each trait.…”
Section: Crop Sciencementioning
confidence: 79%
“…The primary aim of this research was to estimate the variation among the included perennial ryegrass populations for turfgrass dark green color, ground cover, density, and quality when managed by replacing only 60% of the weekly evapotranspiration with irrigation and with two mowing heights. New cool‐season turfgrass cultivars, including perennial ryegrass, will need adaptation to deficit irrigation for continued production in irrigated settings (Braun et al., 2022a; 2022b). We found substantial variation within these populations for each of the four traits and found that the population variation was the largest source of variation for each trait.…”
Section: Discussionmentioning
confidence: 99%
“…Pruning tree roots generally occurs at the boundary where the rough and fairway adjoin in locations where tree roots may compete with turfgrass for water resources, resulting in reduced turfgrass quality. Research efforts into breeding turfgrass have resulted in a wide selection of drought‐tolerant cool‐ and warm‐season turfgrasses (Braun et al., 2022; Katuwal et al., 2022). The wider selection and availability of drought‐tolerant turfgrasses is likely to be a primary reason why more facilities are adopting their use.…”
Section: Resultsmentioning
confidence: 99%